The Development of Multimedia Computer Graphics Learning in Supporting Learning during the Covid-19 Pandemic - Zulkifli N; Handy Ferdiansyah; Mardhatillah Mardhatillah (Edumaspul: Jurnal Pendidikan, 2021)
The objectives of this research were, (1) to develop a prototype of multimedia learning in Computer Graphics course, (2) to test the validity, practicality, and effectiveness of learning multimedia developed in Computer Graphics course. This research was a Research and Development (R&D) design with ADDIE model include thirty students as a sample. The procedure of this research until implementation stage. Instrument of the research was a questionnaire. Data of need analysis obtained based on the review of the exist curriculum, the characteristics of the materials and students need. The students need media that is not only in the conventional form of the file that just containing text but more than it, the media which is able to provide experience directly in the multimedia form that containing images, text, animation, and videos. The multimedia design of computer graphics learning is specifically designed from the structure, contents, menu placement, color selection, and so on to make it easier for lecturers and students. The results of this research are: (1) The results of the analysis of the data validity of the media are in the very valid category, this is obtained from the expert validation of material and media. (2) The results of the evaluation of the students' trials and the lecturers' responses to this multimedia are very practical. (3) this learning multimedia was effective as seen from the recapitulation of the pre-test and post-test learning outcomes assessment showing a significant increase in student learning scores.